Training to Enhance Ecoprint Products Based on the Natural Potential in the National Environment - Nurhaida Nurhaida; Muflihati Muflihati; Munadian Munadian (GUYUB: Journal of Community Engagement, 2024)
The communities that live in the neighborhood of national parks have restrictions on the use of the forests around them; this is related to the rules that protect the national park as a conservation area. It often creates conflict between the public and the government. Sustainable use of forests by using non-wood forests as raw materials for the production of ecoprint products can be one of the solutions. Faculty of Forestry has an obligation to assist the government in ensuring the sustainability of the forests around the national parks. This activity aims to transfer science by introducing ecoprint products that can use the potential of the surrounding nature in a sustainable way. The method used is perform a presentation and direct practice of producing ecoprint products. This activity was accomplished through the collaboration between Bukit Baka Bukit Raya National Park and the Ella Belaban Village, which had about 35 participants. The success of this activity is evaluated through the  questionnaires before and after the activity. Based on the results of the questionnaire, there is an increase in public understanding of ecoprint products over 65%.